The Influence of Lifestyle, Café Atmosphere, and Price Perception on Consumer Purchase Intention at “Kedai Kopi Dari Hati” in Gianyar District - I Dewa Nyoman Putra Setiawan; Made Mulia Handayani; I Made Adi Suwandana (Inisiatif Masyarakat Jurnal Indonesia (IMAJI), 2025)
This study aims to examine the influence of lifestyle, café atmosphere, and price perception on consumer purchase intention at Kedai Kopi Dari Hati in Gianyar District. The research is driven by the rapid growth of the coffee shop industry in Indonesia, which has transformed coffee drinking from a habitual activity into a social lifestyle phenomenon. A quantitative approach was employed, involving 96 respondents selected through purposive sampling. Data were analyzed using multiple linear regression to assess both simultaneous and partial effects. The results revealed that lifestyle, café atmosphere, and price perception have positive and significant impacts on consumer purchase intention. This indicates that a well-designed café environment, lifestyle congruence, and appropriate pricing strategy are key determinants of purchase behavior. The findings highlight the importance of aligning product and experience attributes with consumer values to sustain competitiveness in the café industry..